RELATIONS BETWEEN INSTRUCTOR FEEDBACK, SELF-REGULATION, ASSIGNMENT COMPLETION AND ACADEMIC ACHIEVEMENT IN THAI HIGHER LEARNING INSTITUTIONS (Malaysian Journal of Learning and Instruction, 2021)
Purpose – Assignments have been linked with various benefits, including a higher quality of learning and academic achievement. The purpose of this study was to explore the relationship between assignment completion and academic achievement in higher education. Specifically, it investigated the impact of instructor feedback and three constructs of self-regulation (self-efficacy, time management, and help-seeking) on assignment completion (time spent on assignments and number of assignments completed) and academic achievement.Methodology – The study employed a correlational research design and a self-report survey. Data was collected from 1,106 undergraduate students in six universities in Thailand through a convenience sampling approach. Structural equation modelling was used to establish the strength of the relationships among the constructs of the model.Findings – The number of assignments completed was found to have a strong association with academic achievement. Time management was the strongest predictor of the number of assignments completed as well as time spent on assignments. Time management was also the mediator between self-efficacy and the number of assignments completed. However, help-seeking was negatively associated with both the number of assignments completed and academic achievement.Significance – These results have educational implications, and should be helpful for instructors, instructional designers and educators who may use the information to offer undergraduate students appropriate learning tools, strategies and environments for supporting assignment completion and academic achievement.